Comparison of clinical trial versus non-clinical trial treatment outcomes of childhood acute lymphoblastic leukemia using comparable regimens. Issue 3 (15th March 2016) - Jastaniah, Wasil; Elimam, Naglla; Abdalla, Khalid; Felimban, Sami; Abrar, Mohammed Burhan
Abstract : Objectives : Treatment regimens tested in major clinical trials, conducted by cooperative groups, are often adapted as standard of care by cancer centers with the hope to replicate the treatment outcomes reported in these landmark studies. It is therefore postulated that applying clinical trial regimens in a non-clinical trial setting yield similar outcomes. The aim of the present study was to explore this hypothesis in the context of childhood acute lymphoblastic leukemia (ALL) in our institution. Methods : We retrospectively evaluated 224 consecutive pediatric ALL cases treated between January 2001 and December 2007. Standard-risk (SR) patients were treated on CCG-1991 (regimen OD) while high-risk (HR) patients were treated on CCG-1961 (regimen D). Results were compared with those of the equivalent regimen in the original clinical trials. Statistical analysis was carried using chi-square or Fisher's exact test, Kaplan–Meier and log-rank tests. Results : Comparison of treatment outcomes revealed that SR patients had inferior 5-year overall survival (OS) of (89.0 ± 2.9 vs. 96.0% ± 0.9%); event-free survival of (82.3 ± 3.5 vs. 88.7% ± 1.4%); and relapse rate of (15.8 vs. 9.3% ( P  = 0.034)) compared to patients treated in the clinical trial. However, no statistically significant difference in treatment outcomes was observed between HR patients. Conclusions : Despite using comparable regimens, suboptimal outcomes were noted in SR patients implying that similar treatments do not necessarily yield similar outcomes. This underscores the need to evaluate outcomes of adapted regimens to identify areas that need further improvement in centers not enrolling patients on prospective collaborative clinical trials.